Nucleation and growth inhibition of biological minerals by cementum attachment protein‐derived peptide (CAP‐pi). (24th August 2020) - Montoya, Gonzalo; Lopez, Kevin; Arenas, Jesús; Zamora, Claudia; Hoz, Lía; Romo, Enrique; Jiménez, Karina; Arzate, Higinio
Abstract: Biomineralization is a highly regulated process where proteins/peptides‐crystal interactions contribute to the shaping, phasing and aggregation of minerals. We have identified and synthesized a cementum attachment protein‐derived peptide (CAP‐pi), which corresponds to amino acids 40–53 of the N ‐terminal CAP domain (MASSDEDGTNGGAS) and its phosphorylated variant (MASpSpDEDGTNGGASp) (CAP‐pip). The peptide is composed of polar and negatively charged amino acids, which are disordered, according to in silico analysis. Our results show that CAP‐pi inhibits hydroxyapatite (HA) formation and growth. However, it possesses low capacity to inhibit calcium oxalate crystal growth. CAP‐pip showed a stronger inhibitory effect on the formation and growth of HA. As well as a high capacity to inhibit calcium oxalate monohydrate growth, mainly due to adsorption on specific growth faces. Small peptides have many advantages over the full‐size protein, including low‐cost production and modulation characteristics that allow for structural changes. Our findings suggest that CAP‐pip‐derived peptide could possess therapeutic potential to prevent or treat pathological calcifications such as renal stones and vascular calcification. Abstract : CAP‐pi's assembly as observed by AFM revealed that CAP‐pi at 0.5 µg/ml concentration forms nanospheres. However, at 1.0 µg/ml concentration, it promotes the formation of aggregates. The morphology of the CaOx crystals treated with CAP‐pi at 0.5 µg/ml concentration shows aggregates and fused crystals. At 1 µg/ml concentration, CAP‐pi crystals show rough surfaces with loss of structure. Calcium oxalate crystals treated with CAP‐pip at 0.5 and 1.0 µg/ml showed dramatic effects on crystal growth habits and favored pyramidal morphologies.